Asynchronous project-based learning: Is it effective in biology learning process? - Setiyo Prajoko; Ika Sukmawati; Sekar Jati Pamungkas; Karunia Galih Permadani; Muhammad Radian Nur Alamsyah; Ericka Darmawan (Biosfer: Jurnal Pendidikan Biologi, 2023)
This study aims to determine the effectiveness of the Project-Based Learning model conducted via online (e-PjBL) on the concept understanding of evaluation in the biology learning. A quasi-experimental method with a non-equivalent pre-test and post-test group design is chosen in this study. The research is carried out at the Biology Education Study Program of Universitas Tidar in March - June 2021. A total of 63 college students become the sample in this research which are divided into experimental class and control class. The instrument used to collect the data is in the form of a concept understanding test about the evaluation of biology learning. Then, the results of the data are analyzed by quantitative. The results show that there is no difference in the use of online Project-Based Learning models on the concept understanding of evaluation in biology learning. This is indicated by the results of hypothesis test which is 0.184 > 0.05. Meanwhile, the average N-Gain in the experimental class is 0.2083 which belongs to the ineffective category. Next, several factors become obstacles to the online Project-Based Learning that causes this learning model to be ineffective.